Queen palm fruit selection and foraging techniques of squirrels in the Atlantic Forest - Alves, Briza Cristina [UNESP]; Mendes, Calebe Pereira [UNESP]; Ribeiro, Milton Cezar [UNESP] (Wiley, 2018)
Queen palm seeds (Syagrus romanzoffiana) are a vital source of nutrients for Ingram's squirrel (Guerlinguetus ingrami), a common inhabitant of the Atlantic forest biome of Brazil. G. ingrami acts as both a seed predator and disperser of this important palm; however, little is known about how G. ingrami selects or efficiently opens queen palm seeds. The objectives of this study were to: (1) investigate the squirrel's capacity to determine the germinal orifice among the fruit's three pores, which permits more efficient opening of the fruit; (2) assess whether the thickness and size of the fruit endocarp influence the squirrel's palm selection during foraging; and (3) evaluate whether the rodents preferentially select fruits with invertebrate infestations. To answer these questions, we used a series of behavioral experiments measuring patterns of squirrel feeding behavior (fruit opening, fruit selection, and patch selection), controlling for environmental variables. We found that (1) squirrels identify the queen palm germinal pore by its greater relative depth to the other pores; (2) the average size and thickness of fruit does not influence the squirrel's choice of palm for foraging; and (3) squirrels preferentially consume fruits infested by invertebrates. The development of methods for more efficient processing of queen palm fruit highlights the importance of this resource for G. ingrami. In addition, due to its preferential selection of infested fruits, G. ingrami may benefit palms by reducing parasite population loads.
Keywords: animal behavior; Atlantic forest; feeding strategy; germinal pore; Guerlinguetus ingrami; intraguild predation; Syagrus romanzoffiana